Power Energy Management and Control Strategy Study for Extended-range Auxiliary Power Unit. (December 2016) - Zhang, Hong; Fu, Lin; Song, Jiajian; Yang, Qiangqiang
Abstract: This paper describes a coordination control procedure in auxiliary power unit (APU) power source system for a range extended electric vehicle (RE–EV). Based on the characteristics of urban traffic conditions, the matching on power and selection on parts for the power system of RE-EV is carried on aiming to improve the power and economy. A more economical region for the APU is determined and two kinds of optimization strategy routes are proposed. The coordination control strategy on engine and generator is studied. Simulation results show that the proposed strategy improves the control performance of fuel economy and easy to realize. The comprehensive power control strategies are verified on APU test bench and good agreement with simulation analysis.